The role of CD74 in cardiovascular disease - Li, Qiu-Lin; Tang, Jing; Zhao, Ling; Ruze, Amanguli; Shan, Xue-Feng; Gao, Xiao-Ming (Frontiers in Cardiovascular Medicine, 2023)
Leukocyte differentiation antigen 74 (CD74), also known as invariant chain (Ii), is a transmembrane glycoprotein that is non-polymorphic. CD74 acts as a molecular chaperone for MHC class II molecules that are involved in the antigen presentation of exogenous antigens. The MIF/CD74 pathway acts in conjunction with CXCR2 and CXCR4 to act as a chemotactic agent for monocytes and T lymphocytes, thereby contributing to atherosclerosis. CD74 is also a high-affinity receptor for MIF/D-DT, forming receptor complexes with CD44, CXCR2 and CXCR4 to activate various signaling pathways such as AMPK, NF-κB, and ERK, all of which play important regulatory roles in ischemia-reperfusion (I/R) injury, acute myocardial infarction (AMI), pressure overload-induced myocardial hypertrophy, and arrhythmias. Small molecule inhibitors targeting CD74 therapy have also made real progress. In this review, we concentrated on the role of CD74 in cardiovascular diseases.